Avaliação do papel das moléculas CD80 e CD86 expressas por monócitos na ativação dos linfócitos T CD4+ e no direcionamento de um perfil pró-inflamatório/imunomodulatório nas diferentes formas clínicas da doença de Chagas - Bruna Fernandes Pinto (2020)
Chagas disease, caused by the protozoan Trypanosoma cruzi, was discovered in 1909, but remains a serious public and economic health problem in many countries in Latin America, with approximately 8 million people infected worldwide. During the chronic phase of the disease, individuals can be classified as indeterminate clinical forms (IND), characterized by the absence of symptoms, or cardiac (CARD) when the clinical manifestations result in progressive damage to the cardiac tissue. The mechanisms underlying the development of severe forms of Chagas disease remain poorly understood, however, the study of the immune response is crucial to determine the evolution of the disease. CD80 and CD86 co-stimulatory molecules expressed by monocytes and their subsets induce lymphocyte activation, thereby triggering the subsequent adaptive immune response. The aim of this work was to evaluate the role of CD80 and CD86 co-stimulatory molecules in monocytes and their subsets in targeting the different CD4+ T lymphocytes subsets (Th1, Th2, Th17, Treg), after in vitro stimulation with T. cruzi, in the different clinical forms of Chagas disease. The results showed high CD86 expression in all monocyte subsets only in IND compared to the NI group. After T. cruzi stimulation, IND also showed high frequency of CD4+CTLA-4+ Tlymphocytes when compared to NI individuals. By linear regression analysis we observed an association between CD80 and CD28, and between CD86 and CTLA-4, with a high proportion of Treg cells in IND patients. Next, we evaluated the role of CD80 and CD86 in targeting the Th1, Th2, Th17, Treg subsets through an assay using blockade for CD80 or CD86 in PBMC fromNI, IND and CARD individuals. We demonstrated reduction in the frequency of CTLA-4+ Treg lymphocytes in anti- CD86 culture only in IND group. In addition, Treg showed higher expression of CTLA-4 when compared to other subsets. We found an increase of Th1 CD28+ frequency in the presence of anti-CD86 antibody, as well as a higher frequency of Th2 and Th17 in the CARD group. We observed that in the presence of anti-CD80 there was an increase in the Treg and Treg CTLA- 4+frequency, while anti-CD86 reduced the frequency of these populations only in the IND group. In CARD patients, anti-CD80 leads to a reduction of Treg and Treg CTLA-4+ frequency, and the presence of anti-CD86 leads to an increase in Treg CTLA-4+. We found that in the presence of anti-CD86, CD80 may be related to CTLA-4 expressed by Th2 and Th17, however CD80 presents a negative correlation only with the CTLA-4 by Treg cells of the IND group. Finally, we evaluate the role of CD80 and CD86 molecules in the development of the immune response mediated by T CD8+ and CD8+ regulatory T lymphocytes. We showed a higher frequency of CD8+Treg CD28+ in CARD patients and, CD8+Treg, CD8+Treg IL-10+ and CD8+Treg CTLA-4+ in the IND group. We observed a negative correlation between CD8+Treg CD28+ with monocytes in anti-CD80 culture and, between CD8+Treg CTLA-4+ with patrolling monocytes in anti-CD86 culture. We conclude that Th2 and Th17 lymphocytes can be activated through the interaction between CD80/CTLA-4 receptors in asymptomatic patients and we suggest that Th1 lymphocytes are activated through the interaction between CD80/CD28 in CARD patients. In addition, we proposed that the CD86 receptor may be involved in immunoregulation due to its association with CTLA-4, being decisive in the activation of Treg lymphocytes only in asymptomatic patients. However, Treg cells from CARD patients can be activated alternatively via interaction between CD80/CTLA-4 receptors. Therefore, we concluded that CD86 is a key molecule in the interaction with CTLA-4 and activation of regulatory lymphocytes, mainly in asymptomatic patients, and may represent a new strategy to control inflammation and tissue damage in patients with Chagas disease.